Localização de fontes de descargas parciais baseada em técnicas radiométricas - Duarte , Rafael Moura (2016)
One way to diagnose the level of electrical insulation degradation is to identify the occurrence of partial discharges (PD). Early detection of defects in insulation enables the programming of electric power equipment maintenance activities. Thus, the electrical system can operate more reliably and with fewer interruptions. In addition to detection, the information provided by pulses of partial discharges allow the location of its source. In this work, the main objective is to develop a hybrid technique of location, based on the time-of-arrival and the energies of PD signals. The performance of the hybrid technique was compared with three other location radiometric techniques. For this purpose, the methods used to estimate time-of-arrival of PD pulses and localization techniques are explained in details. In order to make simulations of this work was to develop a model of ray tracing, which is able to simulate the propagation of the pulse wave environments defined by maps. These results were obtained from four simulation scenarios: free space with noise, room with obstacles and without noise, high-voltage substation without noise and high-voltage substation with noise. The performance of the hybrid technique was inferior to that of the location techniques that depend only on the time-of-arrival, the accuracy is not as affected by multipath. However, the estimate provided by the hybrid technique proves useful as an initial condition for non linear time-of-arrival non linear technique.